Respostas

2014-05-16T01:30:12-03:00
P(x)=-5
a)P(1) = (1)^3 - 5(1)^2 + (1) -1 = 1-5+1-1 = -4
b)P(-1) = (-1)^3 - 5(-1)^2 + (-1) -1 = -1 - 5 - 1 - 1 = -8
c)P(-2) = (-2)^3 - 5(-2)^2 + (-2) - 1 = -8 - 20 - 2 - 1 = -31
d)P(3) = (3)^3 - 5(3)^2 + (3) - 1 = 27 - 45 + 3 - 1 = -16
e)P(0) = 0^3 - 5(0)^2 + 0 - 1 = 0 - 0 + 0 - 1 = -1
f)P(1\2)=(  \frac{1}{2})^{3} -5( \frac{1}{2})^2+( \frac{1}{2})-1 \\  \frac{1}{8}- \frac{5}{4}+ \frac{1}{2}-1 \\  \frac{1}{8}- \frac{10}{8}+ \frac{4}{8}- \frac{8}{8}= \frac{1-10+4-8-1}{8}= \frac{-14}{8}= \frac{-7}{4}